Neutrophil function response to aerobic and anaerobic exercise in female judoka and untrained subjects - Wolach, B.; Falk, B.; Gavrieli, R.; Kodesh, E.; Eliakim, A. (British Journal of Sports Medicine, 2000)
OBJECTIVES: Recent studies have indicated reduced immunity in trained athletes. AIM: To assess the effects of aerobic and anaerobic exercise on the phagocytic process in 18-26 year old trained female judoka (n = 8) and untrained controls (n = 7). METHODS: Each subject participated randomly in two different testing sessions (aerobic, 20 minutes of treadmill running at 70-80% of maximal heart rate; anaerobic, Wingate anaerobic test). Venous blood samples were drawn before, immediately after, and 24 hours after each session. RESULTS: There were no significant differences in basal values of net chemotaxis (chemotaxis--random migration), bactericidal activity, and superoxide anion release between the judoka and the untrained women. There was a significant decrease in net chemotaxis 24 hours after the aerobic exercise in both the judoka (from 64 (19) to 39 (13) cells/field, p < 0.02) and the untrained controls (from 60 (7) to 47 (12) cells/field, p < 0.05). Bactericidal activity and superoxide anion release did not change significantly after aerobic exercise in either group. There were no significant changes in net chemotaxis, bactericidal activity, and superoxide anion release after anaerobic exercise in either the judoka or untrained women. CONCLUSIONS: The decrease in net chemotaxis after aerobic, but not after anaerobic, exercise, suggests that net chemotaxis is affected by the combination of exercise intensity and duration, and not by the exercise intensity itself. Similar effects of both exercise sessions in the judoka and the untrained women suggest that training had no effect on neutrophil function response to aerobic and anaerobic exercises.